O impacto da fragmentação e perda de habitat na diversidade de aves em ambientes urbanos - Dri, Gabriela Franzoi (2020)
Biodiversity loss in urban environments is mainly caused by habitat loss and fragmentation. While habitat loss can lead to immediate diversity reduction, fragmentation can isolate biological communities, decreasing species richness over time. Although species diversity in cities is well studied, there are no predictions on long-term species reduction. Besides, there are no integrative study addressing the impact of urbanization on species diversity and on ecological traits associated to species ecosystem function. Therefore, I quantified the short and long- term impact of habitat loss and fragmentation caused by urbanization on bird species extinction and immigration rates, based on fragments area and isolation. Besides, I investigated the roles of environmental variables (e.g. area, isolation, noise and habitat type – urban, suburban, natural) in structuring of bird communities, in terms of functional and phylogenetic diversity. Birds survey and environmental data collection were performed at 43 urban forest fragments in the Santa Catarina Island, municipality of Florianópolis, Santa Catarina, Brazil, during the spring season of 2018, from September to November. To measure the short and long-term effects of urbanization on species richness, accounting for species detectability and the effect of anthropic noise on species occupancy, I implemented a Bayesian model based on the Island Biogeography Theory. I found that area was the main predictor for bird species richness, in which larger fragments had lower extinction rates. Immigration rate also influenced species richness: less isolated fragments had higher immigration rates. Species richness was constant over time, evidencing small extinctions debts, i.e. habitat loss has short-term effect on bird species. I also found that species richness was higher in natural fragments, while higher functional richness occurred at suburban fragments, suggesting different functional groups in the transition between natural and highly urbanized areas. In addition, I found a replacement pattern of taxonomic and phylogenetic composition along the urbanization gradient, indicating that some species are sensitive to anthropic activities, mainly noise pollution. Therefore, these imply that increase of area and decrease of noise are important predictors for maintaining bird diversity in urban areas, useful for sustainable urban planning.